Short communication: An overview of the trematodes fauna of pool frog Pelophylax lessonae (Camerano, 1882) in the Volga Basin, Russia: 1. Adult stages - IGOR V CHIKHLYAEV; ALEXANDER B RUCHIN; ALEXANDER I FAYZULIN (Smujo International, 2018)
Abstract. Chikhlyaev IV, Ruchin AB, Fayzulin AI. 2018. Short communication: An overview of the trematodes fauna of pool frog Pelophylax lessonae (Camerano, 1882) in the Volga Basin, Russia: 1. Adult stages. Nusantara Bioscience 10: 256-262.  The paper presents data on fauna of trematodes of a pool frog Pelophylax lessonae (Camerano, 1882) from 13 regions of the Volga basin (Russia). It consolidates data from different authors over the past 80 years, supplemented by our own research results. There are authentically known findings of 19 trematodes species at an adult stage of development. Three species of trematodes make the basis of helminth fauna: Pneumonoeces variegatus, Opisthioglyphe ranae and Diplodiscus subclavatus. By all species of helminths the following data are provided: taxonomic position, localization, area of detection, biology, definitive hosts, geographic distribution and the degree host-specificity.